Komparasi Keterampilan Menulis Teks Laporan Hasil Observasi dengan Keterampilan Menulis Teks Cerpen Siswa Kelas XI SMA Negeri 1 Payakumbuh - Reski Amelia; Yulianti Rasyid (AHKAM, 2025)
This study is motivated by the differing complexities between factual and narrative texts in high school writing instruction, which affect students' writing proficiency outcomes. The aim of this research is to describe students' skills in writing observational report texts, describe their skills in writing short stories, and analyze the comparison between the two among Grade XI students at SMA Negeri 1 Payakumbuh. A quantitative approach was employed using a descriptive-comparative design. The sample consisted of 30 students selected through proportional random sampling. The research instruments included performance-based writing tests and an assessment rubric covering structure, content, and diction. Data were collected through two writing assignments and analyzed using descriptive and inferential statistics, including a t-test. The results showed that students’ writing skills for observational report texts were in the Very Good category (average score 88.78), while their skills in writing short stories fell into the Good category (average score 76.25). The t-test revealed a significant difference between the two writing skills (tₕᵢₜᵤₙg = 5.66 > tₜₐᵦₑₗ = 1.69), thus supporting the alternative hypothesis. This study contributes to a better understanding of the need for adaptive writing instruction tailored to the distinct characteristics of factual and narrative texts in order to optimize student mastery of both forms.